Lope de Vega y Diego Velázquez (con Caravaggio y Carducho): historia y razones de un silencio - Sánchez Jiménez, Antonio (My University, 2013)
This article explores the reasons behind the conspicuous absence of mentions of Diego Velázquez in Lope de Vega’s works, examining the relationship and ideological coincidences between the poet and the painter. To do so, we analyze Velázquez’s career during Lope’s life and the social links that united or separated the two, suggesting that one of the latter, Vicencio Carducho, was the reason behind Lope’s silence in regards to Velázquez. We advance this hypothesis examining the respective aesthetic ideologies of Lope, Velázquez, and Carducho, and paying special at-tention to Caravaggio’s role in the work of the lat-ter. Finally, we use these deductions to reflect about Lope’s relationship with painting and about his gen-eral modus operandi in the literary field of the time., Este artículo explora las razones sobre la sangrante ausencia de menciones de Diego Veláz-quez en las obras de Lope de Vega examinando en detalle la relación y concomitancias entre el Fénix y el genial pintor sevillano. Para ello, analizamos la si-tuación de la carrera de Velázquez durante la vida de Lope y estudiamos los vínculos sociales que les unían y separaban, sugiriendo que uno de estos úl-timos, Vicencio Carducho, fue el motivo por el que Lope nunca citó a Velázquez. Esta hipótesis la sos-tenemos examinando las ideologías estéticas res-pectivas del Fénix, Velázquez y Carducho, y pres-tando especial atención al papel de Caravaggio en la obra de éste. Por último, empleamos estas deduc-ciones para reflexionar sobre la relación de Lope y la pintura y sobre el modus operandi del poeta en ge-neral en su campo literario.
Lope de Vega and Diego Velázquez (with Caravaggio and Carducho): the Story of a Silence
Keywords: Lope de Vega; Diego Velázquez; Vin-cencio Carducho; Caravaggio; theories on imitation; natural talent; Lope de Vega; Diego Velázquez; Vincencio Carducho; Caravaggio; teorías de la imitación; talento natural